PROSPECTS/POSSIBILITIES OF USING CHAT GPT FOR CREATING METADATA FORLIBRARY RESOURCES - SOKIL, MARIIA; ANDRUKHIV, ANDRIY (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Advanced natural language processing technologies empower the development of intelligent systems capable of analyzing and comprehending text across various domains, including scientific publications, books, and other informational resources. This paper delves into the potential application of the artificial intelligence model ChatGPT within academic libraries, specifically focusing on metadata creation processes for library resources. Given the substantial resource investment required for metadata creation, description, cataloging, and adherence to globally recognized standards, the viability of leveraging modern technologies for such tasks is paramount. ChatGPT offers broad applicability in automating and enhancing the cataloging and description process of diverse documents. Serving as an artificial intelligence-based text generation system, ChatGPT can automatically generate metadata from textual descriptions of resources using sophisticated natural language processing algorithms. This capability streamlines and expedites resource cataloging processes, ultimately assisting library staff and information technology professionals in saving valuable time and effort. Furthermore, this paper discusses the potential of ChatGPT in generating metadata for various material types, ranging from scientific articles to websites and audio-visual recordings, while adhering to standards such as Dublin Core, MARC 21, and UNIMARK. Additionally, the article addresses potential challenges and limitations associated with using the ChatGPT model for metadata generation, including considerations of accuracy and text quality. Overall, this article explores a crucial aspect of applying artificial intelligence in the library field and highlights features and considerations concerning the use of the ChatGPT model for automatic metadata generation in library resources.
Keywords: artificial intelligence (AI); - language models; internet resources; information resources; library resources; Dublin Core; MARC 21; UNIMARK